An American Example of Islamic Chaplaincy Education for the European Context - Vinding, Niels Valdemar (Religions, 2021)
Against the background of increasing political and academic interest in imam and chaplaincy training and education in Europe, this article argues that the value and purpose of such education remains situated in an alignment between educational provider, student-participants, and employer-stakeholder expectations. These expectations are primarily about Muslim students’ learning and development, requirements and standards of employers, and contributions to community and society, and only secondly, the educations aim at meeting political expectations. The article explores aspects of Hartford Seminary’s success with its programme and alignment of education content and environment with student expectations and the labour market demand. This is supported theoretically by the input-environment-outcome assessment model. The structural and contextually embedded criteria for excellence are discussed and problematised, pointing both to the marginalisation of other drivers of education development that are not market aligned and to strategies of embedding religious authority with chaplains in institutions rather than with imams in mosques. In conclusion, the article highlights the self-sustaining logics that drive educational development but also points to corroborating social, economic, and welfare reasons for quality imam and chaplaincy education.